Prognostic Role of Fasting Remnant Cholesterol with In-Stent Restenosis After Drug-Eluting Stent Implantation - Luo Y; Cui S; Zhang C; Huang R; Zhao J; Su K; Luo D; Li Y (International Journal of General Medicine, 2022)
Yinhua Luo,1,* Shengyu Cui,2,* Changjiang Zhang,2 Rui Huang,2 Jinbo Zhao,3 Ke Su,3 Dan Luo,3 Yuanhong Li3 1Department of Central Hospital of Tujia and Miao Autonomous Prefecture, Hubei University of Medicine, Shiyan, People’s Republic of China; 2Department of Cardiology, Renmin Hospital of Wuhan University, Wuhan, People’s Republic of China; 3Cardiovascular Disease Center, Central Hospital of Tujia and Miao Autonomous Prefecture, Hubei University of Medicine, Enshi Prefecture, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yuanhong Li, Cardiovascular Disease Center, Central Hospital of Tujia and Miao Autonomous Prefecture, Hubei University of Medicine, Enshi Prefecture, People’s Republic of China, Email lyh0101@vip.163.comObjective: In-stent restenosis (ISR) is regarded as a critical limiting factor in stenting for coronary heart disease (CHD). Recent research has shown that fasting residual cholesterol (RC) has been shown to have a substantial impact on coronary heart disease. Unfortunately, there have not been much data to bear out the relationship between RC and ISR. Then, the predictive value of RC for in-stent restenosis in patients with coronary heart disease was analyzed.Patients and Methods: Aiming to explore the relationship between RC and ISR, we designed a retrospective study of patients with CHD after drug-eluting stent (DES) implantation, combining the data from a public database and selecting the best-fitting model by comparing the optical subset with least absolute shrinkage and selection operator (LASSO) regression.Results: Analysis of the abovementioned two models showed that the optical subset optimal subset model, which was based on RC, creatine, history of diabetes, smoking, multi-vessel lesions (2 vessels or more lesions), peripheral vascular lesions (PAD), and blood uric acid, had a better fit (AUC = 0.68), and that RC was an independent risk factor for ISR in the abovementioned two models. Notwithstanding its limitation, this study does suggest that RC has good predictive value for ISR.Conclusion: Remnant cholesterol is an independent risk factor for in-stent restenosis after percutaneous coronary intervention (PCI) and is a reliable predictor of ISR.Keywords: in-stent restenosis, ISR, percutaneous coronary intervention, PCI, remnant cholesterol, RC, drug-eluting stents, DES, least absolute shrinkage and selection operator, LASSO